2006
DOI: 10.1111/j.1748-5827.2006.00165.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial tarsal arthrodesis and botulinum toxin A injection for correction of tarsal arthrogryposis in a cat

Abstract: An 11-week-old, domestic shorthair cat was presented for evaluation of a congenital right tarsal deformity. The cat was non-weightbearing lame on the right hindlimb. There was severe tarsal hyperextension and concurrent spasticity/contracture/shortening of the gastrocnemius muscle-tendon. The cat was otherwise healthy. Radiographically there was luxation of the proximal intertarsal joint and talocrural hyperextension. Treatment with 10 mu/kg botulinum toxin A (Botox; Allergan) intramuscular injections directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 22 publications
3
7
0
3
Order By: Relevance
“…We recommend surgical correction for the cases in which conservative management failed and the deformity is inflexible. Partial tarsal arthrodesis with a laterally applied 1.5 mm / 2.0 mm diameter seven-hole veterinary cuttable plate in a 15-week-old cat was reported to be successful (7). Similarly, pantarsal arthrodesis with a transarticular external fixation demonstrated excellent long-term functional efficacy for both of the limbs in our study.…”
Section: A B Csupporting
confidence: 73%
See 4 more Smart Citations
“…We recommend surgical correction for the cases in which conservative management failed and the deformity is inflexible. Partial tarsal arthrodesis with a laterally applied 1.5 mm / 2.0 mm diameter seven-hole veterinary cuttable plate in a 15-week-old cat was reported to be successful (7). Similarly, pantarsal arthrodesis with a transarticular external fixation demonstrated excellent long-term functional efficacy for both of the limbs in our study.…”
Section: A B Csupporting
confidence: 73%
“…Also, Boute and colleagues reported that the tibio-tarsal joints of all three kittens could be flexed to an angle of approximately 135° (6). Interestingly, we could not obtain even a slight improvement in our case, in both standing or under deep sedation, similar to the right hindlimb of the kitten reported by Bright and colleagues (7). Because of that, partial tarsal arthrodesis was performed in that unilateral case.…”
Section: A B Csupporting
confidence: 45%
See 3 more Smart Citations